Jogo de cartas adaptável e contextualizável para a interpretação de imagens no Ensino de Artes Visuais - Gomes, Silvia Trentin (2019)
This research aims at presenting a model of an adaptive and context aware card game that may be integrated to a digital system in the teaching-learning process of visual arts. The concepts of imagination and social interaction, as delineated by Vygotsky, and curiosity, defined by Paulo Freire, based the design of this game. This proposal intends to provide the students/players with the opportunity to reflect upon the production of their knowledge as they interpret images selected to be used in the game. The need for this research lies on the quantity of visual information without contextualization to which we are currently exposed as well as on the relevance acquired by them when used to stimulate imagination, interaction and curiosity in the process of learners’ cognition. Due to its structure, the process of creating this card game enables the insertion of artistic images that are related to the contents to be taught and to the learners’ realities. By using this model, teachers/mediators may stimulate learners to read and research about images in order to elaborate the game and reflect upon its interpretation while playing it. The player explains his/her interpretation of the “rules of action” in the game (which can be drawings, sounds, gestures or utterances) in order to establish a relationship between what was observed in the image and what he/she had previously researched about it. This study is grounded in the ideas of Vygotsky (2009), who encourages the artistic creation, once, for him, human knowledge is constructed by stimulating creative imagination and our production is resultant from the observation of the environment and mediation with “the other” in social interaction. This is a qualitative exploratory field research. It involved children and adolescents aged from 10 to 14 who were taking visual arts lessons (drawing and painting) in non formal learning contexts. It was noticed that the model of game proposed here is an ally for the personalization of teaching because, while being created, it enabled the learners to read and research about the images used, and in the act of playing, it demanded the interpretation and contextualization of those images. Therefore, the development and playability present in this kind of ludic production comprise a model of generation of sensitive and intelligible knowledge that may enable the intervention of learners and teachers in the educational process. The aim of this intervention is to stimulate a protagonist role of the learner by action-reflection, reflection-action upon a contextualized expression using both current digital and analogical means available